Safety and Efficacy of Different Approaches for Catheter Ablation of Para-Hisian Accessory Pathway - El-Damaty, Ahmed; Mahmoud Maarek, Mahmoud Ahmed; Shaaban Ali , Ahmed; Abdel hady, Yasser Ahmed (Journal of Neonatal Surgery, 2025)
Background and purpose: Radiofrequency (RF) catheter ablation is recognized as a final treatment for atrioventricular accessory pathways (AP). In experienced centers, the success rate of accessory pathways ablation exceeds ninety-five percent accompanied by a low rate of complications. To investigate the outcomes from various methods for radiofrequency ablation of para-Hisian AP regarding efficacy and safety. Patients and Methods: This observational analytical study included patients who had RF catheter ablation for a para-hisian AP at Kasr Al-Ainy University hospital and Beni-Suef University hospital EP lab over a period of 24 months from January 2020 to January 2022. Patients were enrolled prospectively and retrospectively through chart review. Forty-five patients had a para-hisian AP that have been successfully ablated thorough different approaches. Results: Retrograde AVN Wencbach cycle length (AVN WCL) was significantly increased in post ablation compared by pre ablation in the three studied groups with a statistically significant p-values (p-value <0.001). Conclusion: With accurate and careful mapping, it is relatively safe to ablate para-hisian accessory pathways. if probable, proper extension of ablation duration may diminish the recurrence rate of para-Hisian accessory pathways. The majority of para-Hisian APs may be effectively and safely ablated via iIVC-A, but ablation in the NCC or SVC is neither an early nor a preferred technique. The degree of local ventriculo-atrial fusion in the para-Hisian region throughout retrograde atrioventricular accessory pathways conduction may predict or distinguish the successful ablation location.